Measurement of BUM Desa Development: A Literature Study (Forum Ilmu Sosial, 2020)
The growth in the number of BUM Desa (Village-Owned Enterprises) is increasing in line with the issuance of the Village Law. The number of BUM Desa, which currently reaches 47,717 units, should be appreciated. However, in light of its development, it is necessary to observe it from various sides, not only in terms of quantity but also in terms of quality. Therefore, it is essential to study how a conceptual review of the measurement of BUM Desa development. The purpose of this research is to carry out a literature study to determine the conceptual description of the development of BUM Desa. This study uses a non-systematic literature review method by exploring the literature and the results of previous studies related to the development of BUM Desa. The results of the study show that BUM Desa is a business entity that has the characteristics of a social enterprise, commercial institution, and local enterprise that form an integral part of the management of BUM Desa. Measuring the development of BUM Desa needs to consider these three characteristics in compiling its parameters and indicators. Therefore, BUM Desa can be said to be developing if it has succeeded in running social enterprises, commercial enterprises, and local enterprises. There is no standard in measuring the development of BUM Desa that can be used as a reference in general, so there are many different thoughts on the matter. Alternative parameters that need to be considered in measuring the development of BUM Desa include social value, civil society, innovation, financial perspective, customer perspective, business process perspective, growth and learning perspective, local potential and local wisdom.